The Human Resource Development and Product Innovation of MSMEs in Kendari City - Asraf, Asraf; Hakim, Abdul; Bagea, Arfin; Paluala, Kusman (Jurnal Ilmiah Manajemen Kesatuan, 2024)
This study aims to explore the influence of Human Resource (HR) development on product innovation in Micro, Small, and Medium Enterprises (MSMEs) in Kendari City. The main focus is how improved HR competencies can contribute to innovative product development in the context of local MSMEs. This study used descriptive qualitative analysis involving 30 MSMEs in Kendari. Data was collected through in-depth interviews, observations, and documentation studies. This approach allows researchers to gain a broader understanding of the internal dynamics of MSMEs and their influence on product innovation. The results showed that of the MSMEs that invested in HR development, 70% of respondents recognized that training and continuing education are essential investments for improving the quality of employees, which will influence skills development, and tend to result in more significant product innovation. The research also identified several challenges, including limited resources and access to relevant training. Investment in HR development is a key factor in driving product innovation in Kendari MSMEs. However, there needs to be further efforts to overcome existing barriers, including through government support and educational institutions. This study recommends further research with a mixed approach to deepen the understanding of the relationship between HR development and innovation in MSMEs.